The changing landscape of telemedicine in Sarawak - Sharifah Aishah, Wan; Teh, Cheng Lay; Cheong, Yaw Kiet; Ling, Guo Rey; Chuah, Seow Lin; Kueh, C.; Liew, C.; Ahmad Tirmizi, Jobli (John Wiley & Sons, Inc., 2024)
Background/Purpose: Healthcare providers in remote areas or in areas with limited rheumatologists depend on telemedicine for rheumatology consultations and shared patient management. The COVID-19 pandemic presented an increased challenge, where even previously accessible patients were rendered inaccessible due to travel restrictions. This required all of us to utilize available technology to provide comprehensive rheumatological management, and also presented a unique opportunity for a shift in telemedicine methods. One recently developed telemedicine method was conducting virtual rheumatology meetings with the district hospitals in Sarawak for rheumatology case discussions. We aimed to explore the various methods of telemedicine between district hospitals and rheumatologists and the participants’ perception of the benefits of attending the virtual meetings. Methods: We specifically examined the utilization of telemedicine in Rheumatology consultations and shared patient management in the Sarawak district hospitals. Regular virtual rheumatology interhospital meetings were started in August 2022 and a survey was conducted in January 2024 among the participants. Results: When rheumatology services were first established in Sarawak in 2006, rheumatology consultatons via telemedicine were conducted using phone calls and emails. In 2009, the era of smartphones added instant messaging with attached photos of physical findings and laboratory results. During the COVID-19 pandemic, we increasingly relied on these methods for consultations. Subsequently, virtual meeting platforms became increasingly. In August 2022 we started 2-monthly virtual rheumatology meetings via Google Meet. The objectives of the programme were to discuss challenging rheumatology cases and to expand rheumatology knowledge among participants. The case discussions between the participants from the various district hospitals and the panel of rheumatologists also allowed for a wider audience simultaneously. We conducted a survey of 29 participants in a virtual meeting in January 2024, which comprised of 19 medical officers and 10 physicians. 11 participants (37.9%) attended for the first time, 11 participants (37.9%) have attended >3 times, while 7 participants (24.1%) have attended 1 or 2 times previously. 3 participants (10.3%) described the virtual meeting as having ‘some benefit’ in increasing their rheumatology knowledge, while 26 participants (89.7%) described the sessions as ‘very beneficial’. All participants agreed that 216 of 259 | ABSTRACT attending the virtual meetings improved their patients’ management and would recommend it to others. Conclusion: The methodology of telemedicine in Sarawak have evolved from phone consultations to email and smartphone instant messaging with photo attachments and now virtual meetings that can accommodate many participants simultaneously. Participants of the virtual meetings have described the meetings as beneficial.